Pengaruh Understaffing terhadap Stres Kerja Pegawai: Peran Dukungan Sosial sebagai Variabel Moderasi - Kurniawati, Fitria Dwi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This study aims to analyze the effect of understaffing on employee work stress with the role of social support as a moderating variable. This study focuses on employees of PT XYZ, a company facing operational challenges due to labor shortages. The research method used was quantitative with an explanatory approach, involving 29 employees selected through purposive sampling. The analysis was conducted using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results showed that understaffing has a significant positive influence on job stress. In addition, social support was shown to positively moderate the relationship, which means that social support can weaken the negative impact of understaffing on job stress. These findings support the Job Demand-Resource (JD-R) theory and provide practical implications for management to improve employee well-being through social support programs. This study also makes a theoretical contribution in understanding the role of work resources in managing high job demands.